2014
DOI: 10.1155/2014/351263
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Leakage at Implant-Abutment Connection of Three Implant Systems Having the Same Prosthetic Interface Using Rhodamine B

Abstract: Objectives. Hollow space between implant and abutment may act as reservoir for commensal and/or pathogenic bacteria representing a potential source of tissue inflammation. Microbial colonization of the interfacial gap may ultimately lead to infection and bone resorption. Using Rhodamine B, a sensitive fluorescent tracer dye, we aim in this study to investigate leakage at implant-abutment connection of three implant systems having the same prosthetic interface. Materials and Methods. Twenty-one implants (seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In another study by Aloise et al [ 10 ], bacterial leakage was observed in 2 of 10 implants with internal conical connection. Berberi et al [ 11 ] used internal connection implants in their study and bacterial leakage was confirmed in them. Dibart et al [ 20 ], who reported no leakage, assessed the presence of bacterial leakage for only 72 h. An explanation for this diversity in results may be due to differences in Morse design and tapering degrees in the investigated implant samples.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In another study by Aloise et al [ 10 ], bacterial leakage was observed in 2 of 10 implants with internal conical connection. Berberi et al [ 11 ] used internal connection implants in their study and bacterial leakage was confirmed in them. Dibart et al [ 20 ], who reported no leakage, assessed the presence of bacterial leakage for only 72 h. An explanation for this diversity in results may be due to differences in Morse design and tapering degrees in the investigated implant samples.…”
Section: Discussionmentioning
confidence: 92%
“…Berberi et al [ 11 ] studied the three brands of implant systems with the same 11° conical connection and concluded that the tested connections appear to be unable to prevent leakage. Although the accuracy in fabrication and the precision of fit of the components seem to be an important factor in resistance to leakage, nevertheless, we utilized a CE approved 11° Morse taper connection randomly from available brands in the market.…”
Section: Discussionmentioning
confidence: 99%
“…One implant brand with two different implant types, diameters, and wall thickness were evaluated. However, commonly used CC implant's connection has been copied by other commonly used manufacturers 57 . A performance similar to CC implant's may be expected from those implants, which copied CC's connection.…”
Section: Discussionmentioning
confidence: 99%
“…A performance similar to CC implant's may be expected from those implants, which copied CC's connection. However, future studies are required to compare implants with similar connections as different brands may have differences in implant diameter, taper angle, wall thickness, alloy, inner volume, and insertion torque values 57 . Future studies should also be performed to investigate the screw stability of abutments on implants with different connections.…”
Section: Discussionmentioning
confidence: 99%
“…Also important in the design of dental implants is the implant/ abutment connection. Multiple in vitro and clinical investigations have shown that a conical connection in combination with internal platform switching reduces micro movements and thus bacterial contamination by propelling sulcus fluid, which results in marginal bone loss [34,35,50]. With its combination of characteristics, the investigated newly designed implant system seems to meet the requirements for a successful dental implant system.…”
Section: Discussionmentioning
confidence: 99%